DETERMINANTS OF TAXPAYERS’ INTENTION AND USE OF THE CORE TAX ADMINISTRATION SYSTEM: EVIDENCE FROM INDIVIDUAL AND CORPORATE TAXPAYERS IN GREATER MALANG - Uliasari, Agustina; Amin, Annisa’ Abiyyu; Juzaila, Dini Shinta; Pardosi, Hilda Tamara; Aprilia, Rislah Winda; Anggraini, Zahra Ayu (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
The digital transformation of tax administration is a key policy instrument to address tax system complexity and persistent compliance challenges in Indonesia. In line with this agenda, the Directorate General of Taxes introduced the Core Tax Administration System (CTAS) in January 2025 to integrate fragmented tax applications into a centralized platform. However, empirical evidence on taxpayers’ acceptance and actual use of CTAS remains scarce. This study addresses this gap by applying the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) to examine the determinants of taxpayers’ behavioral intention and use behavior. Using an explanatory quantitative design, data were collected from 159 individual and corporate taxpayers in the Greater Malang area through convenience sampling between July 1 and July 29, 2025. The data was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that performance expectancy, effort expectancy, and social influence significantly affect behavioral intention, while facilitating conditions exert a strong influence on CTAS use behavior. Although behavioral intention is positively associated with use behavior, the relationship is not statistically significant, suggesting that actual system use in the early implementation phase is shaped more by infrastructural readiness and institutional support than by intention alone. This study provides novel post-implementation evidence on CTAS adoption and highlights the critical role of perceived usefulness, ease of use, social influence, and facilitating conditions in sustaining digital tax system utilization.